Música nacional como factor motivacional en el desarrollo artístico de los estudiantes que integran la estudiantina de la Unidad Educativa Quevedo - Martinez Cajas, Walter Patricio (2017)
National music as a motivational factor in the artistic development of the students that make up the estudiantina is a decisive factor in the teaching-learning process of this musical genre. Therefore, motivated students show interest in their activities, feel efficient and try to achieve successful tasks, generally using cognitive, self-regulating and specific strategies. Similarly, motivated teachers feel they can help their students learn to sing and sing our national music, by devoting extra time to planning and instructional work to make sure they are learning and mastering knowledge and skills defined as objectives of the students, in this case of the Educational Unit Quevedo. This research aims to promote national music as a motivational factor, in the formation of the student population of the Educational Unit Quevedo. The theoretical framework based on the inductive and analytical method allowed to determine the pertinent conclusions. The types of research applied, such as descriptive, explanatory and participatory, allowed the techniques used in this study, such as observation, interview and questionnaire, to help in the development of the research. Therefore, this research allowed us to know the level of knowledge about the importance of national music and the need to strengthen the school students, of which, the suggested proposal makes known more broadly the idea that you have on the subject, and justify the conclusion: that is, the development and preparation for the estudiantina of the educational institution.